Means of artistic expressiveness in advertisement - Калініченко, О. В. (Proceedings of National Aviation University, 2021)
In the given article is underlined topicality of the meaning of optimum means of artistic expressiveness in creation of the effective advertisement. A wide spectrum of both stable and the newest means of artistic expressiveness that are used according to results of marketing research and the advertisement tasks aiming at the improvement of its artistic and aesthetic qualities is analysed.